MORTGAGE FINANCING AND HOUSING DEVELOPMENT IN NIGERIA - Udoka, Chris O.; Kpataene, Mary (International Journal of Research -GRANTHAALAYAH, 2017)
This study examined mortgage financing and housing development in Nigeria. The main focus of this research was to ascertain the impact of mortgage loan in housing development in Nigeria. To achieve this objective, data were extracted from CBN statistical bulletin and National Bureau of Statistics from 1990 to 2014. Three hypotheses were formulated and tested using econometric models such as Augmented Dickey-Fuller unit root test, the co-integration tests revealed the existence of a long-run relationship among the variables. The Error Correction Model established causal links and dynamic interactions between variables by granger causality test. The result of the findings showed a significant relationship between mortgage financing and housing development in Nigeria. Variables such as mortgage loan and interest rate had positive and significant impact on housing development while cost of building had a negative effect on housing development in Nigeria. Further findings revealed that mortgage bank deposit had positive effect on mortgage investment while inflation had a negative effect on mortgage investment. The study recommended that mortgage institution in Nigeria should develop strategies to mobilize more deposits and explore new sources of fund such as funds from the capital market via housing bonds, savings and loans from co-operative societies. Government should create an enabling environment for private housing sector in housing development in Nigeria by providing infrastructure and enhancing soundness and competitiveness of mortgage institutions in Nigeria.